Religion and politics in the early republic : Jasper Adams and the church-state debate - Dreisbach, Daniel L. (The University Press of Kentucky, 2015)
The church-state debate currently alive in our courts and legislatures is strikingly similar to that of the 1830s. A secular drift in American culture and the role of religion in a pluralistic society were concerns that dominated the controversy then, as now. In Religion and Politics in the Early Republic, Daniel L. Dreisbach compellingly argues that the issues in our current debate were framed in earlier centuries by documents crucial to an understanding of church-state relations, the First Amendment, and our present concern with the constitutional role of religion in American public life. R.